Multiple cranial neuropathies due to sarcoidosis resembling Guillain-Barre syndrome - SHIMOYAMA, Takashi; INOUE, Kiyoharu; OCHIAI, Aya; YAGUCHI, Hiroshi (OTOLOGIA FUKUOKA, 2008)
A 37-year-old male suddenly developed hearing loss in his right ear. He was treated with corticosteroids based on a diagnosis of sudden deafness. The deafness improved and thereafter the steroids were tapered off. He next presented right III, bilateral V, IX, X palsies soon after the steroids were withdrawn. The cell counts and the protein levels were elevated in the cerebrospinal fluid. The MRI findings of the brain were normal. He therefore was diagnosed to have Guillain-Barre syndrome; specifically, acute oropharyngeal palsy based on the rapid course of progression. He was placed on a high dose of intravenous immunoglobulins. However, the symptoms were aggravated and steroid therapy was again started. The multiple cranial palsies improved with steroid treatment. After further investigation with a tuberculin reaction, chest CT, 67Ga scintigraphy and bronchoalveolar lavage, a final diagnosis of multiple cranial neuropathies associated with sarcoidosis was made. The initial deafness was thought to be a part of sarcoid neuropathy. The present case suggests that multiple cranial neuropathies with sarcoidosis may present with rapid progression like Guillain-Barre syndrome.